Cardiovascular and metabolic comorbidities in patients with obstructive sleep apnoea syndrome - FUSETTI, M. (Pacini Editore SpA, 2012)
The purpose of this study was to evaluate the correlation between severity of obstructive sleep apnoea syndrome (OSAS), cardiovascular disease and metabolic syndrome. We recruited 1185 patients with OSAS who underwent a complete ENT examination, including nasolaryngeal fibre optic endoscopy with Müller's manoeuvre, overnight cardio-respiratory monitoring, Epworth Sleepiness Scale (ESS) to measure daytime sleepiness, body mass index (BMI), measurement of blood pressure and blood tests. Subsequently, subjects were divided into three subgroups according to the Apnoea Hypopnoea Index (AHI): mild OSAS (AHI 5-15), moderate OSAS (AHI 15-30) and severe OSAS (AHI > 30). In the sample collected, 347 (262 males and 85 females) of 1185 patients suffered from mild OSAS, 363 (269 males and 94 females) from moderate OSAS and 475 (330 males and 145 females) from severe OSAS. In the group suffering from mild OSAS, we found: 127 patients affected by hypertension, 48 with diabetes, 11 with dyslipidaemia and 32 with metabolic syndrome. In the group with moderate OSAS there were 157 patients with hypertension, 63 with diabetes, 72 with dyslipidaemia and 47 with metabolic syndrome. In the group suffering from severe OSAS there were 244 patients with hypertension, 138 with diabetes, 47 with dyslipidaemia and 90 with metabolic syndrome. For data analysis, we used the Spearman correlation test adjusted according to Sidak between the dependent variable AHI and the independent variables BMI, ESS, average SO2 (SO(2med)), hypertension, diabetes mellitus, dyslipidaemia and metabolic syndrome. The results show different patterns of correlation in terms of statistical significance: BMI ρ(s) = 0.26, SO(2med) ρ(s) = -0:51, hypertension ρ(s) = -0.05, dyslipidaemia ρ(s) = 0.22 for women, and BMI ρ(s) = 0.53, ESS ρ(s) = 0.28, SO(2med) ρ(s) = -0.50, hypertension ρ(s) = 0.17, diabetes mellitus ρ(s) = 0.28 and metabolic syndrome ρ(s) = 0.26 for men. The results of the study confirm the existence of a statistically significant correlation between the severity of OSAS and BMI, ESS, average SO2, hypertension, diabetes mellitus, dyslipidaemia and metabolic syndrome.